Attitude Determination System For Nano Satellite Using Extended Kalman Filter On Arm7tdmi Platform - Keui, Adam Ain Mohd Poin (2014)
Extended kalman filter (ekf) has been successfully utilized in satellites missions. However, in comparison to other attitude determination methods developed, it is one of the most computationally burdening algorithm and with the new development of using nano satellites which have limited electrical power, mass, space and usually budget, it is essential to design an attitude determination system (ads) which conforms to this limitation. Therefore, in this thesis, as a computational improvement on the innosat project, the rcm3400 microcontroller of the ads is replaced with the arm7tdmi based microprocessor to test its capability. The arm7tdmi has been chosen since it is one of the well-known microprocessor used in various electronic equipment because it is low power and robust. The embest s3cev40 development board used, houses the s3c44b0x microprocessor which is an arm7tdmi microprocessor. The testing is done by connecting the development board to a personal computer which has been installed with the arm interface software based on visual basic 6.0.